2015
DOI: 10.1111/cfs.12240
|View full text |Cite
|
Sign up to set email alerts
|

Parents in high‐conflict custodial cases: negotiating shared care across households

Abstract: A B S T R AC TUnderstanding the dynamics of custodial conflicts is important for reducing the level of such conflicts and improving the upbringing conditions for the children involved. The parents in these cases care for children living in two households, and our approach therefore draws on the knowledge of how 'ordinary' parents proceed in sharing care within and between locations. The paper is based on qualitative interviews with 15 Norwegian parents who were in contact with the child protection service duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
2
16
0
4
Order By: Relevance
“…The participants who talked about being positioned as a 'parent in conflict' described interactions with child welfare professionals who primarily seemed to define their custodial disagreements as the 'trouble', yet simultaneously excluded these 'troubles' from child welfare work. As in the previous set of narratives, these participants talked about themselves as concerned parents (Jevne and Andenaes 2015), presenting worries about their ex-partner's parenting practises. However, their narratives indicated that the caseworkers took a neutral position (Jevne and Ulvik 2012;Saini et al 2012), positioning both parents as equally responsible for the situation.…”
Section: Parent In Conflictmentioning
confidence: 98%
See 4 more Smart Citations
“…The participants who talked about being positioned as a 'parent in conflict' described interactions with child welfare professionals who primarily seemed to define their custodial disagreements as the 'trouble', yet simultaneously excluded these 'troubles' from child welfare work. As in the previous set of narratives, these participants talked about themselves as concerned parents (Jevne and Andenaes 2015), presenting worries about their ex-partner's parenting practises. However, their narratives indicated that the caseworkers took a neutral position (Jevne and Ulvik 2012;Saini et al 2012), positioning both parents as equally responsible for the situation.…”
Section: Parent In Conflictmentioning
confidence: 98%
“…Among the three client positions, the 'legitimately concerned parent' was the position to which most participants in this study aspired. These participants positioned themselves as concerned parent (Jevne and Andenaes 2015), mobilising a client position for themselves and their child and CWS's assistance primarily based on their claims that their ex-partner was a problematic and inadequate co-parent. Furthermore, these participants gave accounts of interactions with caseworkers, who seemed to operate with similar problem constructions, thus offering them a client position they seemed to accept.…”
Section: Legitimately Concerned Parentmentioning
confidence: 99%
See 3 more Smart Citations